ChemInform Abstract: Copper(I)‐Catalyzed Heterocyclization of α‐Acyl‐α‐alkynyl Ketene Dithioacetals: Synthesis of 3‐Cyanofurans. Issue 36 (August 2016) - Wang, Lianjie; Liu, Xiaocui; Wang, Mang; Liu, Jun
Abstract: The heterocyclization procedure generates a cyano moiety in situ with ammonium acetate as the nitrogen source providing 3‐cyanofuran derivatives in good to excellent yield.